The Deceleration Index - Is it the Missing Link in Rehabilitation? - Chris Wolfe; Phil Page; Michael Voight; Connor Norman; Peter Draovitch (North American Sports Medicine Institute, 2023)
The ability to decelerate is a key component of any successful rehabilitation program, yet it is often overlooked in favor of more traditional forms of rehabilitation and training. Deceleration, which is defined as the ability to reduce speed or momentum and stop or change direction, can be a key component of successful rehabilitation. The deceleration index is a new metric being used by some physical therapists and rehabilitation specialists to improve patient outcomes. The index is based on the principle that deceleration forces should match those created with acceleration. When patients can quickly and efficiently decelerate during physical activity, they are less likely to experience pain or injury. While the deceleration index is still in its early stages of development, there is promising evidence that it could be the missing link in effective rehabilitation. In this editorial commentary, we'll explore what the deceleration index is and why it is important to the rehabilitation process.